Aktivitas Masyarakat Kampung Kali Code Terhadap Pencegahan Kriminalitas - Wulandari Desias; Diah Intan Kusumo Dewi (Teknik PWK (Perencanaan Wilayah Kota), 2019)
Kampung Kali Code is one of the urban villages in the center of Yogyakarta City. Kampung Kali Code development began with the initiative of the community to improve the image of slums to be more organized. The development was carried out through the 3M program (Mundur, Munggah, and Madep), this led to the development of the physical design of the Kampung Kali Code neighborhood. The physical design of the environment is in the form of the existence of regional facilities that will support the activities of the surrounding community. These activities arise due to the need of the community to live comfortably and safely. The purpose of the community that exists for safe and comfortable living can be seen through the generation of activities affecting crime prevention. To help this research a quantitative approach was used by distributing questionnaires spread across 5 RW Kampung Kali Code of Gondokusuman District. From the results of the study, it can be seen that the activities in the Kampung Kali Code occur because of the physical design of the environment in the form of public facilities that create an activity according to the needs of the community. With the existence of these public facilities, crime prevention can be done because the community conducts daily activities in the area provided and will minimize the area prone to crime in Kampung Kali Code itself.